Development of PPT-Based Islamic Religious Education Teaching Materials (Power Point) at SMKN 1 Proppo Pamekasan - Tobi, Tobi; Zainab, Nurul; Maimun, Maimun (Universitas Trunojoyo Madura, 2024)
This research developed Islamic Religious Education Teaching Materials based on PPT (Power Point) through the Research and Development (RD) method, which conducted trials on a large scale and small scale at SMKN 1 PROPPO PAMEKASAN, especially in Class X RPL. With this research, it was found that the proposed teaching materials were suitable for use, proven by the results of student group assignments in the form of concept maps. In its application, the research uses the Borg and Gall learning model. This process includes recognizing possibilities and issues, gathering information, designing the product, validating the design, improving the design, testing the product, and revising the product.